Pendekatan SWOT Pada Produk Boncara Raja (Boncabe Rawit Rawa Jaya) di RPTRA Rawa Jaya Duren Sawit Jakarta Timur - Safira Wiranti; Henita Fajar Oktavia; Tungga Buana Diana; Sugiyanto (Fakultas Pertanian Universitas Borobudur, 2024)
RPTRA Rawa Jaya is in Rawa Jaya Village, Duren Sawit District-East Jakarta. Processing cayenne pepper into Boncara Raja allows the availability of quality food ingredients to be maintained. Boncara Raja, in addition to extending the shelf life of chili, this product also supports increasing consumption needs. SWOT analysis also helps identify that the main strength of the Boncara Raja product is the high demand for chili in East Jakarta, which is driven by the culture of consuming spicy food. In addition, the success of RPTRA Rawa Jaya in cultivating Rawita chili, with its resistance to extreme weather, gives the impression that this commodity has potential. On the other hand, challenges also arise such as dependence on the quality of the harvest and limited marketing capacity. The data collection method in this study uses primary data with a qualitative approach. Based on the SWOT analysis, the Boncara Raja product has a main strength in the use of Rawita chili from its own cultivation, which reduces dependence on external supplies, but this product still faces limitations in production capacity. On the other hand, Boncara Raja still has an opportunity, namely the taste of Boncabe suits the taste and consumer segment who like spicy and practical food, but Boncara Raja still must meet consumer demands for halal labels which affect Boncara Raja products to be able to follow this demand.